Adhesive composition, wafer-level packaging structure, preparation method of wafer-level packaging structure and semiconductor device

By using adhesive compositions of alicyclic epoxy compounds, cationic initiators, cationic stabilizers and nanofillers, the problems of high interface stress, easy glue leakage and poor chemical resistance in embedded packaging are solved, and higher packaging is achieved Reliability and durability.

CN119463769APending Publication Date: 2025-02-18SHANGHAI WINSCENE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411550131.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, the adhesive layer between the chip and the substrate in the embedded packaging has problems such as high interface stress, easy glue overflow, and poor chemical resistance, which is difficult to meet the needs of miniaturization and high reliability of electronic products.

Method used

Using an adhesive composition including alicyclic epoxy compounds, cationic initiators, cationic stabilizers and nanofillers, the fluidity and curing shrinkage of the adhesive are adjusted through the cationic curing technology and the thixotropy of the nanofillers, and the fluidity and curing shrinkage rate of the adhesive are improved. Chemical resistance and heat resistance.

Benefits of technology

It effectively reduces the interface stress between the pit filler and the silicon substrate, avoids glue spills, improves the reliability and durability of the packaging, and maintains stability under high temperature or chemical corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463769A_ABST
    Figure CN119463769A_ABST
Patent Text Reader

Abstract

The invention provides an adhesive composition, a wafer-level packaging structure, a preparation method of the wafer-level packaging structure and a semiconductor device. The adhesive composition of the present invention comprises (A) an alicyclic epoxy compound; (B) a cationic initiator; (C) a cationic stabilizer; and (D) a nanofiller. The adhesive composition disclosed by the invention has low curing shrinkage rate and good thixotropic property, adverse effects of an adhesive overflow phenomenon on the appearance and performance of a product can be avoided in a construction process, and the obtained cured resin has the advantages of small volume shrinkage rate, good chemical resistance, good normal-temperature storage performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of packaging materials, and in particular to an adhesive composition, a wafer-level packaging structure and a preparation method thereof, and a semiconductor device. Background Art

[0002] Embedded chip packaging is an advanced electronic packaging technology that embeds the chip directly into the substrate material, enabling higher integration, smaller package size, and improved electrical performance. This technology typically requires creating a groove in the substrate slightly larger than the chip size, then embedding the chip into the groove. However, if the groove bottom is uneven or the upper opening is smaller than the bottom, this can affect chip embedding. In these cases, a filler is often used to fill the groove defect to prevent it from affecting subsequent packaging processes.

[0003] Traditional substrate pit filling methods typically use light-curing acrylate adhesives to repair and fill groove defects. These adhesives are primarily composed of acrylate monomers or oligomers, supplemented by photoinitiators, which impart certain fluidity and adhesion. When exposed to specific wavelengths of light, such as ultraviolet or visible light, the photoinitiators generate free radicals, which trigger polymerization of the acrylates. This solidifies the adhesive and forms a strong, solid product, thus filling the pit.

[0004] With the development trend of miniaturization of electronic products, chips also need smaller package size, and the groove size in substrate is also getting smaller and smaller. This has just put forward higher requirements for the adhesive for filling. For example, it needs good fluidity to fill, but it is necessary to avoid that fluidity is too good and causes glue to overflow the groove surface. There is also higher requirement for the curing shrinkage of adhesive. The curing shrinkage is larger and can cause interfacial stress between adhesive and substrate, which not only affects the adhesion between chip and silicon substrate, but also may cause the peeling or failure of filling pit glue from groove surface, affecting the reliability of packaging. In addition, the chip after packaging also needs to be installed in printed circuit board with other semiconductor devices to form a complete electronic system. In the process such as rewiring or ball planting, solvents or solutions such as cyclopentanone, n-hexane, quaternary ammonium aqueous solution, propylene glycol monomethyl ether acetate are inevitably exposed. This requires adhesive to have excellent chemical resistance to avoid being eroded. Existing acrylic adhesives are difficult to meet the above-mentioned needs. Therefore, developing a novel adhesive that can meet the above-mentioned needs is a technical problem to be solved in this area. Summary of the Invention

[0005] The present invention provides an adhesive composition, a wafer-level packaging structure and a preparation method thereof, and a semiconductor device, so as to at least solve the problems existing in the prior art of the adhesive layer between the chip and the substrate in the embedded packaging, such as high interfacial stress, easy adhesive overflow, and poor chemical resistance.

[0006] The first aspect of the present invention provides an adhesive composition comprising: (A) an alicyclic epoxy compound; (B) a cationic initiator; (C) a cationic stabilizer; and (D) a nanofiller.

[0007] The adhesive composition as described above, wherein the alicyclic epoxy compound includes one or more of 7-oxabicyclo[4,1,0]heptane-3-carboxylic acid, bis-7-oxabicyclo[4,1,0]heptane, vinylcyclohexene dioxide, dipolycyclopentadiene dioxide, tetrahydroindene diepoxide, and (3,4,3',4'-diepoxy)bicyclohexane.

[0008] The adhesive composition as described above, wherein the component (A) further comprises an oxetane compound, wherein the oxetane compound has a structure shown in Formula 1 or Formula 2:

[0009]

[0010] In Formula 1, R1 is a hydrogen atom, a C1-C6 alkyl group, a C1-C6 fluoroalkyl group, an allyl group, a C6-C30 aryl group, a furyl group, or a thienyl group; R2 is a C1-C6 alkyl group, a C2-C6 alkenyl group, a C2-C6 alkylcarbonyl group, a C2-C6 alkoxycarbonyl group, or a C2-C6 N-alkylcarbamoyl group;

[0011] In formula 2, R3 and R4 are each independently selected from a hydrogen atom, a C1-C6 alkyl group, a C1-C6 fluoroalkyl group, an allyl group, a C6-C30 aryl group, a furyl group or a thienyl group; L1 is a C1-C6 alkylene group, a poly(alkyleneoxy) group, a C2-C6 alkenylene group, a carbonyl group, a C2-C6 alkylene group containing a carbonyl group, a C2-C6 alkylene group containing a carboxyl group, or a C2-C6 alkylene group containing a carbamoyl group.

[0012] As described above, the adhesive composition, wherein the oxetane compound includes one or more of bis[(3-ethyloxetane-3-yl)methyl]benzene-1,3-dicarboxylate, 4,4-bis[(3-ethyl-3-oxoethyl)methoxymethyl]biphenyl, 3-ethyl-3-oxetane methanol, 3-ethyl-3-(4-hydroxybutoxymethyl)oxetane, and 3-ethyl-3-[(benzyloxy)methyl]oxetane polymer.

[0013] In the adhesive composition as described above, the mass ratio of the alicyclic epoxy compound to the oxetane compound is 10:1 to 1:10.

[0014] In the adhesive composition as described above, the cationic initiator is selected from sulfonium salt cationic initiators and / or ammonium salt cationic initiators;

[0015] Preferably, the sulfonium salt cationic initiator has a structure shown in Formula 3:

[0016]

[0017] In formula 3, R5, R6, and R7 are each independently selected from a substituted or unsubstituted C1-C6 alkyl group or a substituted or unsubstituted C6-C20 aryl group, and X1 is selected from Cl - 、BF4 - PF6 - 、N(CF3SO2)2 - 、CH3CO2 - CF3CO2 - CF3SO3 - 、HSO4 - 、SO4 2- 、AsF6 - 、SbF6 - and B(C6F5)4 - One of the following;

[0018] The ammonium salt cationic initiator has the structure described in Formula 4:

[0019]

[0020] In formula 4, R8, R9, R 10 、R 11 Each independently selected from a substituted or unsubstituted C1-C6 alkyl group or a substituted or unsubstituted C6-C20 aryl group, X2 - Selected from Cl - 、BF4 - PF6 - 、N(CF3SO2)2 - 、CH3CO2 - CF3CO2 - CF3SO3 - 、HSO4 - 、SO4 2- 、AsF6 - 、SbF6 - and B(C6F5)4 - One of them.

[0021] The adhesive composition as described above, wherein the cationic stabilizer comprises one or more of the sulfonium salt compound represented by Formula 5, triphenylphosphine, triethanolamine, and 18-crown ether-6;

[0022]

[0023] In formula 5, R 12 to R 16 Each independently represents a hydrogen atom, a C1-C6 alkyl group, an acetyl group, a C1-C6 alkoxycarbonyl group, a benzoyl group or a benzyloxycarbonyl group, and R 17 and R 18 Each is independently a C1-C6 alkyl, benzyl, o-methylbenzyl, m-methylbenzyl, p-methylbenzyl or naphthylmethyl, and Z is a C1-C6 alkylsulfate.

[0024] The adhesive composition as described above, wherein the nanofiller is selected from one or more of silicon dioxide, silicon carbide, boron nitride, diamond, aluminum oxide, aluminum hydroxide, vermiculite, mica, wollastonite, calcium carbonate, titanium dioxide, quartz sand, glass, barium sulfate, zirconium oxide, carbon black and organic fillers;

[0025] And / or, the particle size of the nanofiller is 10 nm to 100 nm.

[0026] The adhesive composition as described above comprises, by mass content, 70 wt% to 95 wt% of component (A), 1 wt% to 10 wt% of component (B), 0.1 wt% to 1.0 wt% of component (C), and 0.5 wt% to 30 wt% of component (D).

[0027] The second aspect of the present invention provides a wafer-level packaging structure, comprising a silicon substrate and a plurality of grooves located on the silicon substrate, wherein the grooves contain chips, and the gaps between the chips and the grooves contain a cured product of the adhesive composition provided in the first aspect.

[0028] A third aspect of the present invention provides a method for preparing the wafer-level packaging structure as described above, comprising the following steps:

[0029] embedding the chip into the groove of the silicon substrate;

[0030] injecting the adhesive composition into the gap between the chip and the groove;

[0031] The adhesive composition is cured to obtain the wafer-level packaging structure.

[0032] The preparation method as described above, wherein the curing temperature is 100-180° C., and the curing time is 30 min-180 min.

[0033] A fourth aspect of the present invention provides a semiconductor device, comprising the wafer-level packaging structure provided by the second aspect of the present invention or the wafer-level packaging structure manufactured by the manufacturing method of the third aspect of the present invention.

[0034] The implementation of the present invention has at least the following beneficial effects:

[0035] (1) The present invention selects a low-viscosity cationic-cured alicyclic epoxy resin as the adhesive component of the adhesive composition for the pit-filling glue. Its curing reaction is not affected by moisture in the air, the cured product is colorless and transparent, and the curing shrinkage is small. This can not only effectively reduce the interfacial stress between the pit-filling glue and the silicon substrate and improve the performance of the product, but also avoid product deformation caused by excessive shrinkage, and is conducive to the product obtaining good optical properties.

[0036] (2) The adhesive composition of the present invention has good chemical resistance and heat resistance. It will not age or deform even at high temperatures (>250°C) or chemical corrosion, and can still maintain good stability in the subsequent semiconductor manufacturing process of packaging.

[0037] (3) The present invention adds a nanofiller with a thixotropic effect to the adhesive composition, so that the adhesive composition has good fluidity during construction and is convenient for filling pits. In a static state, the viscosity increases and the fluidity deteriorates, thereby avoiding the risk of glue overflow. This not only improves the appearance quality of the product, but also avoids the problem of product performance degradation caused by glue overflow.

[0038] (4) The present invention regulates the initiation activity of the cationic initiator by adding a cationic stabilizer to the adhesive composition, thereby preventing it from initiating the curing of the epoxy monomer at room temperature, thereby facilitating the storage of the adhesive composition at room temperature and reducing its storage and transportation costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 is a schematic diagram of a wafer-level packaging structure according to an embodiment of the present invention;

[0040] Figure 2 This is a microscope observation image of the groove filling portion of Example 1;

[0041] Figure 3 This is a microscope observation picture of the groove filling in Example 2.

[0042] Description of reference numerals:

[0043] 101: Silicon substrate;

[0044] 102: chip;

[0045] 103: Groove. DETAILED DESCRIPTION

[0046] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific embodiments listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts are within the scope of protection of the present invention.

[0047] With the development trend of miniaturization of electronic products, the chip also needs a smaller package size, and the groove size in the substrate is also getting smaller and smaller. This has just put forward higher requirements for the adhesive for filling. It needs good fluidity to fill, but it is necessary to avoid that fluidity is too good and causes glue to overflow the groove surface. There is also a higher requirement for the curing shrinkage of the adhesive. The curing shrinkage is larger and can cause interfacial stress to be generated between the adhesive and the substrate, which not only affects the adhesion between the chip and the silicon substrate, but also may cause the pit-filling glue to peel off or fail from the groove surface, affecting the reliability of packaging. In addition, the chip after packaging also needs to be installed in the printed circuit board with other semiconductor devices to form a complete electronic system. In the subsequent process, it is inevitable to contact solvents or solutions such as cyclopentanone, n-hexane, quaternary ammonium aqueous solution, propylene glycol monomethyl ether acetate, etc. This requires the adhesive to have excellent chemical resistance to avoid being eroded. And the existing acrylic adhesive commonly used as bottom fill glue is difficult to meet the above-mentioned needs. Therefore, it is still necessary to develop an adhesive with lower curing shrinkage, thixotropic property, and chemical resistance to improve the packaging reliability of electronic devices.

[0048] Based on this, the present invention provides an adhesive composition comprising (A) an alicyclic epoxy compound; (B) a cationic initiator; (C) a cationic stabilizer; and (D) a nanofiller.

[0049] In the present invention, the alicyclic epoxy compound refers to an alicyclic ethylene oxide compound, which can be cured under the initiation of a cationic initiator to form an alicyclic epoxy resin. Cationic curing is usually accompanied by low volume shrinkage, and the cyclic structure is also conducive to limiting the freedom of the molecular chain, inhibiting the volume shrinkage caused by the movement of the molecular chain, thereby helping to reduce the interfacial stress between the cured resin and the substrate, improving the performance of the product, and avoiding product deformation caused by excessive shrinkage. In addition, cationic curing does not rely on reaction with water, so it is not very sensitive to moisture. It can still be effectively cured in a humid system, and its application scenarios are more diverse. Moreover, the alicyclic epoxy resin formed after curing has good chemical resistance, low shrinkage and low viscosity. The chemical resistance can protect the encapsulated chip from corrosion by chemical reagents in subsequent processes. The low shrinkage is conducive to reducing interfacial stress and product deformation, ensuring the stability and reliability of the bonding. The low viscosity corresponds to better fluidity, making the adhesive composition more conducive to construction operation in small-sized grooves.

[0050] However, the mixed system of alicyclic epoxy compounds and cationic initiators also has the following defects when used as an adhesive for filling pits: on the one hand, the cationic initiator is too active and can initiate the curing of the alicyclic epoxy compound at room temperature or slightly above room temperature, making the adhesive not suitable for storage at room temperature; on the other hand, although the better fluidity makes it easier to operate during construction, it also increases the risk of glue overflow, which not only affects the appearance of the product but also leads to a decrease in product performance.

[0051] Based on the above-mentioned defects, the present invention adds a cationic stabilizer and a nanofiller to the adhesive composition, wherein the cationic stabilizer can form a complex with the cationic initiator, reduce the activity of the cationic initiator, prevent it from solidifying at room temperature, make it easy to store at room temperature, improve its convenience of use, and reduce storage and transportation costs. The nanofiller can act as a thixotropic agent to form a three-dimensional network structure in the resin. In a static state, this network structure remains stable through physical forces such as van der Waals forces and hydrogen bonds, thereby increasing the viscosity of the system, preventing the adhesive from flowing after being added to the groove of the substrate, and reducing the risk of the adhesive overflowing the groove. During the construction process, this network structure is destroyed, the interaction between the nanofillers is weakened, the viscosity is reduced, and it is easier to flow and apply.

[0052] A larger number of cyclic structures can further limit the freedom of the molecular chain, thereby further reducing volume changes. Based on the above considerations, the alicyclic epoxy compound preferably includes one or more of 7-oxabicyclo[4,1,0]heptane-3-carboxylic acid, bis-7-oxabicyclo[4,1,0]heptane, vinylcyclohexene dioxide, dipolycyclopentadiene dioxide, tetrahydroindene diepoxide, and (3,4,3',4'-diepoxy)bicyclohexane. The above alicyclic epoxy compounds not only have a larger number of cyclic structures that can suppress the volume shrinkage of epoxy resins, but also have good transparency and chemical stability, making the cured material suitable for harsh chemical environments and applications with high optical transparency.

[0053] As a preferred embodiment, component (A) further comprises an oxetane compound having a structure shown in Formula 1 or Formula 2:

[0054]

[0055] In Formula 1, R1 is a hydrogen atom, a C1-C6 alkyl group, a C1-C6 fluoroalkyl group, an allyl group, a C6-C30 aryl group, a furyl group, or a thienyl group; R2 is a C1-C6 alkyl group, a C2-C6 alkenyl group, a C2-C6 alkylcarbonyl group, a C2-C6 alkoxycarbonyl group, or a C2-C6 N-alkylcarbamoyl group;

[0056] In formula 2, R3 and R4 are each independently selected from a hydrogen atom, a C1-C6 alkyl group, a C1-C6 fluoroalkyl group, an allyl group, a C6-C30 aryl group, a furyl group or a thienyl group; L1 is a C1-C6 alkylene group, a poly(alkyleneoxy) group, a C2-C6 alkenylene group, a carbonyl group, a C2-C6 alkylene group containing a carbonyl group, a C2-C6 alkylene group containing a carboxyl group, or a C2-C6 alkylene group containing a carbamoyl group.

[0057] C1-C6 alkyl refers to a straight-chain or branched-chain alkyl group having 1 to 6 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, etc.

[0058] The C1-C6 fluorinated alkyl group refers to a fluorinated straight-chain alkyl group or a fluorinated branched-chain alkyl group having 1 to 6 carbon atoms, for example, a fluorinated methyl group, a fluorinated ethyl group, a fluorinated propyl group, and the like.

[0059] The C6-C30 aryl group refers to a carbocyclic group having 6 to 30 carbon atoms that satisfies the 4n+2 Huckel rule, for example, phenyl, naphthyl, anthracenyl, phenanthrenyl, etc., and the ring may be further connected to a substituent, such as benzyl, fluorobenzyl, methoxybenzyl or phenoxyethyl.

[0060] The C2 to C6 alkenyl group refers to a straight-chain or branched hydrocarbon group having 2 to 6 carbon atoms and containing an unsaturated carbon-carbon double bond, such as ethenyl, 1-propenyl, 2-propenyl, 2-methyl-1-propenyl, 2-methyl-2-propenyl, 1-butenyl, 2-butene, 3-butene, etc.

[0061] The C2-C6 alkylcarbonyl group refers to a carbonyl group having 2 to 6 carbon atoms and containing an alkyl substituent, such as ethylcarbonyl, propylcarbonyl or butylcarbonyl.

[0062] The C2-C6 alkoxycarbonyl group refers to a carbonyl group having 2 to 6 carbon atoms and containing an alkoxy substituent, such as ethoxycarbonyl, propoxycarbonyl or butoxycarbonyl.

[0063] The C2-C6 N-alkylcarbamoyl group refers to a carbamoyl group having an alkyl substituent attached to an amino group having 2 to 6 carbon atoms, for example, N-ethylcarbamoyl, N-propylcarbamoyl, N-butylcarbamoyl or N-pentylcarbamoyl.

[0064] The C1-C6 alkylene group refers to a linear or branched saturated divalent hydrocarbon group having 1 to 6 carbon atoms, such as methylene, ethylene, propylene, butylene, and the like.

[0065] The C2-C6 alkenylene group refers to an unsaturated divalent hydrocarbon group containing a carbon-carbon double bond and having 2 to 6 carbon atoms, such as vinylene, propenylene, butene, and the like.

[0066] The C2-C6 alkylene group containing a carboxyl group refers to a branched or branched saturated divalent hydrocarbon group having 2 to 6 carbon atoms and substituted with a carboxyl group on the side chain.

[0067] Alicyclic epoxy compounds have a fast initiation rate but slow chain growth, typically producing oligomers with molecular weights in the thousands that are hard and brittle. Oxetane compounds, on the other hand, have a slow initiation rate but fast chain growth. When sufficient initiator concentration is reached, they can produce polymers with molecular weights in the tens of thousands. The present invention combines alicyclic epoxy compounds and oxetane compounds to achieve a suitable curing rate and form high-molecular-weight polymers, resulting in a cured product with good ductility and flexibility, creating a more reliable packaging structure.

[0068] As a preferred embodiment, the oxetane compound includes one or more of bis[(3-ethyloxetane-3-yl)methyl]benzene-1,3-dicarboxylate, 4,4-bis[(3-ethyl-3-oxoethyl)methoxymethyl]biphenyl, 3-ethyl-3-oxetanemethanol, 3-ethyl-3-(4-hydroxybutoxymethyl)oxetane, and 3-ethyl-3-[(benzyloxy)methyl]oxetane polymer. When used in adhesive compositions, these oxetane compounds can better regulate the curing rate, increase the molecular weight of the cured product, and thereby improve the temperature and chemical resistance of the cured product.

[0069] Preferably, the mass ratio of the alicyclic epoxy compound to the oxetane compound is 10:1 to 1:10. Within the above mass ratio range, the two can better cooperate with each other, thereby improving the ductility and flexibility of the cured product.

[0070] The present invention does not particularly limit the type of cationic initiator, which can be selected from initiators commonly used in the polymer field and suitable for initiating polymerization of epoxy compounds.

[0071] In a specific embodiment, the cationic initiator is selected from a sulfonium salt cationic initiator and / or an ammonium salt cationic initiator.

[0072] Sulfonium salt cationic initiators can efficiently generate active centers and initiate polymerization reactions. They also have good thermal stability and can be used in a wide range.

[0073] Ammonium salt cationic initiators are generally stable solids, which are beneficial to further improve the storage stability of the adhesive.

[0074] In a preferred embodiment, the sulfonium salt cationic initiator has a structure shown in Formula 3:

[0075]

[0076] In formula 3, R5, R6, and R7 are each independently selected from a substituted or unsubstituted C1-C6 alkyl group or a substituted or unsubstituted C6-C20 aryl group, and X1 is selected from Cl - 、BF4 - PF6 - 、N(CF3SO2)2 - 、CH3CO2 - CF3CO2 - CF3SO3 - 、HSO4 - 、SO4 2- 、AsF6 - 、SbF6 - and B(C6F5)4 -One of them.

[0077] In a preferred embodiment, the ammonium salt cationic initiator has a structure shown in Formula 4:

[0078]

[0079] In formula 4, R8, R9, R 10 、R 11 Each independently selected from a substituted or unsubstituted C1-C6 alkyl group or a substituted or unsubstituted C6-C20 aryl group, X2 - Selected from Cl - 、BF4 - PF6 - 、N(CF3SO2)2 - 、CH3CO2 - CF3CO2 - CF3SO3 - 、HSO4 - 、SO4 2- 、AsF6 - 、SbF6 - and B(C6F5)4 - One of them.

[0080] Among them, the substituents in the substituted C1~C6 alkyl and C6~C20 aryl in Formula 3 and Formula 4 can be selected from methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, n-pentyl, tert-pentyl, isopentyl, hexyl, cyclohexyl, phenyl, anthracenyl and phenanthrenyl, etc.

[0081] The present invention does not specifically limit the type of cationic stabilizer, and it can be selected from cationic stabilizers that are commonly used in the art and can play a complexing role, including but not limited to one or more of the sulfonium salt compound shown in Formula 5, triphenylphosphine, triethanolamine, and 18-crown-6;

[0082]

[0083] In formula 5, R 12 to R 16 Each independently represents a hydrogen atom, a C1-C6 alkyl group, an acetyl group, a C1-C6 alkoxycarbonyl group, a benzoyl group or a benzyloxycarbonyl group, and R 17 and R 18 Each is independently a C1-C6 alkyl, benzyl, o-methylbenzyl, m-methylbenzyl, p-methylbenzyl or naphthylmethyl, and Z is a C1-C6 alkylsulfate.

[0084] Among them, the S atom in the above-mentioned sulfide compound has a strong coordination ability, which can form a stable complex with the cationic initiator and thus reduce its initiation activity; triphenylphosphine is a strong σ-electron donor, which can form a stable coordination bond with the cation through its lone pair of electrons and thus reduce its initiation activity; triethanolamine has three hydroxyl groups and one amino group, which can form a chelate with the cationic initiator and thus reduce its initiation activity; 18-crown-6 is a crown ether compound with a unique cyclic structure, composed of six ethyleneoxy units, and its oxygen atom has a coordination ability, which can complex the cation and thus reduce the initiation activity of its cationic initiator.

[0085] In a specific embodiment, the nanofiller is selected from one or more of silicon dioxide, silicon carbide, boron nitride, diamond, aluminum oxide, aluminum hydroxide, vermiculite, mica, wollastonite, calcium carbonate, titanium dioxide, quartz sand, glass, barium sulfate, zirconium oxide, carbon black, and organic fillers. The organic filler may be wood powder, cellulose, starch, resin microspheres, rubber powder, polyester fiber, etc.

[0086] As a preferred embodiment, the nanofiller is selected from silicon dioxide. In addition to having good dispersibility and enhancing thixotropic effect, nanosilicon dioxide also has good thermal stability and transparency.

[0087] Furthermore, the silicon dioxide may be pyrogenic silicon dioxide. Pyrogenic silicon dioxide, also known as fumed silicon dioxide, is an ultrafine silicon dioxide powder prepared by chemical vapor deposition, which has higher chemical purity and smaller particle size, and exhibits better thixotropic properties.

[0088] The particle size of nanofillers also significantly affects their thixotropic properties. Smaller particles have a higher specific surface area and better dispersion, forming more contact points with the matrix material, which helps form a denser and more stable network structure, thereby making the nanofiller's thixotropic properties even better. Based on the above considerations, the particle size of the nanofiller is controlled to be 10nm to 100nm to achieve better thixotropic properties.

[0089] For example, the particle size of the nanofiller can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or a range consisting of any two of the above values.

[0090] It is understood that the mass content of each component in the adhesive composition affects its bonding strength, curing time, chemical resistance, thixotropic properties, etc. For example, component (A) is a monomer used for curing; increasing its content helps improve the bonding strength and durability between the chip and the groove; component (B) is used to initiate the curing of the monomer; increasing its content helps accelerate the curing speed and improve the initial bonding strength and heat resistance; the content of component (C) is generally proportional to the content of component (B); the higher the content of component (B), the higher the content of component (C) required to control the activity of the cationic initiator; and increasing the content of component (D) helps improve the thixotropic properties of the adhesive, making it easier to apply during the pit filling operation while avoiding the occurrence of adhesive overflow. Based on the above factors, in order to make the adhesive composition have better performance in comprehensive properties such as bonding strength, curing time, chemical resistance, and thixotropic properties, the adhesive composition can be controlled to include 70wt% to 95wt% of component (A), 1wt% to 10wt% of component (B), 0.1wt% to 1.0wt% of component (C), and 0.5wt% to 30wt% of component (D) in terms of mass percentage.

[0091] As a preferred embodiment, the adhesive composition is liquid at 25°C, and has a viscosity of 4.0 Pa·s or less at 25°C.

[0092] More preferably, at room temperature and relative humidity ≤55%, the viscosity increase rate of the adhesive composition after storage for 14 days is less than 200%.

[0093] When the viscosity characteristics of the adhesive composition meet the above characteristics, it is beneficial to maintain good fluidity for easy construction.

[0094] Wafer-level packaging (WLP) is a technology that packages and tests entire silicon wafers before dicing them into individual finished chips. The packaged chips are the same size as the bare die. The resulting chips can be highly miniaturized, and chip costs are significantly reduced as the size of the chips decreases and the wafer size increases. Consequently, the miniaturized chip size places higher demands on the performance of the pothole filler.

[0095] Based on this, the second aspect of the present invention provides a wafer-level packaging structure, Figure 1 FIG. 1 is a schematic diagram of a wafer-level packaging structure according to an embodiment of the present invention. Figure 1 As shown, the packaging structure includes a silicon substrate 101 and a plurality of grooves 103 located on the silicon substrate 101. The grooves 103 include chips 102. The gaps between the chips 102 and the grooves 103 include the cured product of the adhesive composition provided by the first aspect of the present invention.

[0096] Herein, the term "several grooves" means that the present invention does not limit the number of grooves, which may be one or more, but at least one.

[0097] Since the cured product formed by the adhesive composition of the present invention has the advantages of small volume shrinkage, high transparency, good chemical resistance, and good thixotropic properties, it fills the gap between the chip and the groove, effectively bonding the chip and the groove, while also reducing the interfacial stress between the cured product and the substrate and the occurrence of glue overflow, thereby enhancing packaging reliability and giving the product good appearance and performance.

[0098] The size of the groove is also a critical factor in wafer-level packaging, directly affecting chip embedding, package reliability, and the performance of the final product. The groove size needs to match the size of the chip to be embedded. Typically, the groove size is slightly larger than the chip to facilitate chip placement and fixation.

[0099] In a specific embodiment, the length and width of the groove are 1 to 10 mm respectively, and the depth of the groove is 50 to 300 μm. Within the above groove range, the adhesive composition of the present invention exhibits good construction properties, is easy to fill, and is not prone to overflow.

[0100] Experimental studies have shown that the amount of glue overflow can be controlled within the spacing between two adjacent grooves. If the glue overflow is too large and overflows into adjacent grooves, it will cover the chip and prevent it from functioning normally.

[0101] Exemplarily, the length and width of the groove can be 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm or a range consisting of any two of the above values, and the depth of the groove can be 50 μm, 100 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm or a range consisting of any two of the above values.

[0102] The present invention does not impose any particular restrictions on the size of the groove, which can be adapted to the shape of the chip. For example, it can be trapezoidal or rectangular. When the groove is trapezoidal, it is generally necessary to control the upper opening of the groove to be larger than the bottom of the groove to facilitate chip insertion.

[0103] A third aspect of the present invention provides a method for preparing the wafer-level packaging structure as described above, comprising the following steps:

[0104] Embed the chip in a groove in the silicon substrate;

[0105] injecting an adhesive composition into the gap between the chip and the groove;

[0106] The adhesive composition is cured to obtain a wafer-level packaging structure.

[0107] The present invention does not specifically limit the method for forming the grooves in the silicon substrate; the grooves can be formed using conventional groove forming methods in the art. For example, a groove cluster can be formed on the silicon substrate using photolithography, and then a dry or wet etching process can be used to remove the silicon material to form a groove of the desired size. After etching is completed, the groove can be cleaned to remove residual etching byproducts and particles.

[0108] In order to accurately embed the chip into the groove, high-precision pick-and-place equipment can be used to assist in embedding.

[0109] The present invention does not limit the method for injecting the adhesive composition into the gap between the chip and the groove; conventional methods in the art can be used to complete the injection process. For example, an automatic dispensing machine can be used to apply the adhesive composition to the gap between the groove and the chip. The use of a dispensing machine allows for precise control of the amount of adhesive composition applied and the location of the adhesive composition.

[0110] In order to avoid the influence of bubbles on the bonding reliability, the adhesive composition may be mixed and degassed before injection to ensure the uniformity of the adhesive composition.

[0111] After the glue injection is completed, appropriate curing conditions are selected according to the component characteristics of the adhesive composition to cure it.

[0112] In a preferred embodiment, the curing temperature is 100-180° C., and the curing time is 30 min to 180 min.

[0113] Curing within the above temperature and time range can not only complete the curing process efficiently in a shorter time, but also avoid damage to the device caused by excessive temperature.

[0114] Exemplarily, the curing temperature can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C or a range consisting of any two of the above values; the curing time can be 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min, 130min, 140min, 150min, 160min, 170min, 180min or a range consisting of any two of the above values.

[0115] A fourth aspect of the present invention provides a semiconductor device, comprising the wafer-level packaging structure provided by the second aspect of the present invention or the wafer-level packaging structure manufactured by the manufacturing method provided by the present invention.

[0116] The semiconductor device of the present invention has a wafer-level packaging structure formed by curing the adhesive composition as described above, which has the advantages of low curing shrinkage, high transparency, and good chemical resistance. Therefore, its packaging effect is more stable and reliable, and can improve the reliability and service life of the semiconductor device.

[0117] Preferably, the above-mentioned semiconductor devices can be semiconductor packaged devices such as power management chips, radio frequency transceiver chips, baseband processors and high-end network systems.

[0118] The present invention is further described below by way of specific examples. In the following examples and comparative examples, the chemical names, sources, and structural formulas of the raw materials or reagents used are as follows:

[0119] CELLOXIDE 2021P: 7-Oxabicyclo[4,1,0]heptane-3-carboxylic acid, manufactured by Daicel Corporation, with the chemical formula

[0120] CELLOXIDE 8010: Bis-7-oxabicyclo[4,1,0]heptane, manufactured by Daicel Corporation, with the chemical formula

[0121] OXIPA: Bis[(3-ethyloxetane-3-yl)methyl]benzene-1,3-dicarboxylate, manufactured by UBE Co., Ltd., with the chemical formula

[0122] OXBP: 4,4-bis[(3-ethyl-3-oxyethyl)methoxymethyl]biphenyl, manufactured by UBE Co., Ltd., with the chemical structural formula

[0123] SI-110: 4-Hydroxyphenylbenzylmethylsulfonium hexafluorophosphate, Sanshin Chemical Industry Co., Ltd., chemical structure is

[0124] CXC-1612: N-(p-Methoxybenzyl)-N,N-dimethylaniliniumhexafluoroantimonate, King Industries, chemical structure:

[0125]

[0126] SI-S: (4-Hydroxyphenyl)dimethylsulfonium methanesulfonate, Sanshin Chemical Industry Co., Ltd., chemical structure is

[0127] TPP: triphenylphosphine, Hokuko Chemical Industry Co., Ltd., chemical structure is

[0128] YA050C: nano-silica filler, average particle size: about 50 nm, manufactured by Admatechs Co., Ltd.

[0129] TS720: fumed silica, surface area 200m 2 / g, particle size is 5-40nm, manufactured by Cabot Corporation.

[0130] Examples 1 to 10 and Comparative Examples 1 to 3

[0131] In Examples 1 to 10 and Comparative Examples 1 to 3, component (A), component (B), component (C), and component (D) were mixed to prepare an adhesive composition. The types of the components and the weight proportions of the components in the adhesive composition are shown in Table 1.

[0132] Table 1

[0133]

[0134]

[0135] The properties of the adhesive compositions of Examples 1 to 10 and Comparative Examples 1 to 3 were evaluated through the following process.

[0136] 1. Viscosity evaluation

[0137] Test method: Use a Brookfield DVNext lamina viscometer at 25°C and 10 revolutions per minute (RPM) using a CPA-52Z rotor to measure the viscosity of the freshly prepared adhesive composition (initial viscosity, unit: mPa·s) and the viscosity of the adhesive composition after storage at 25°C and 55% relative humidity for 7 days or 14 days. Let (viscosity after 7 days or 14 days) / (initial viscosity) be the viscosity increase rate (unit: %).

[0138] 2. Density and curing shrinkage

[0139] Test Method: Tests were conducted in accordance with ASTM D1875. Samples were 25 mm x 6 mm in size. Density of the adhesive composition was measured before and after curing using a Mettler Instruments ME204 analytical balance with a 0.1 mg accuracy and its solid / liquid density measurement kit. Curing conditions were heating at 150°C for 60 minutes. Curing shrinkage was then calculated using the following formula:

[0140] Curing shrinkage=(density after curing-density before curing) / density before curing×100%.

[0141] 3. Gel time

[0142] Test method: On a hot plate (HS-10, manufactured by IKA) at 150°C, supply 0.5 g ± 0.1 g of the adhesive composition and stir in a circular motion with a stirring rod. The gel time is measured from the start of supply until the string formed when the stirring rod is lifted and separated from the composition becomes less than 5 mm (string length).

[0143] 4. Filling and overflow test

[0144] Test method: Several grooves measuring 2.2mm (L) × 2.2mm (W) × 90μm (D) were etched on a 12-inch wafer (from Huatian Technology Co., Ltd.), with a spacing of 0.3mm between adjacent grooves. At 25°C, an iJET-7H dispensing machine (Guangdong Anda Intelligent Equipment Co., Ltd.) was used to dispense adhesive (i.e., dispense the adhesive composition) into the grooves. The amount of adhesive dispensed into each groove was fixed at 0.7mg. After dispensing, the sample was cured at 150°C for 1 hour. The groove filling was observed under a microscope. An "O" was assigned for a smooth surface with an excess of ≤300μm, and an "X" was assigned for an uneven surface or an excess of >300μm. The excess adhesive could be measured using a CCD camera on the dispensing machine. An excess of >300μm was considered to be excessive if the excess adhesive overflowed into adjacent grooves, obscuring the boundaries between them.

[0145] Figure 2 This is a microscope observation of the groove filling of Example 1. Figure 3 This is a microscope observation picture of the groove filler of Comparative Example 1. Figure 2 and Figure 3 The dark gray part of the gap between two adjacent grooves represents the overflowed glue. Figure 2 and Figure 3 By comparison, it can be seen that the comparative example 1 has obvious glue phenomenon, while the embodiment has basically no glue overflow phenomenon.

[0146] 5. Heat resistance test

[0147] Testing Method: The pyrolysis temperature (5% weight loss temperature, Td5) of the cured adhesive compositions of the Examples and Comparative Examples, formed after curing (curing conditions: curing at 150°C for 60 minutes), was measured using a differential thermal gravimetric analyzer (TGA, manufactured by METTLER TOLEDO). The measurement was conducted under a nitrogen flow rate of 50 mL / min, with the temperature increased from 30°C to 800°C at a rate of 10°C / minute.

[0148] 6. Chemical resistance test

[0149] Test method: The weight change rate of the cured adhesive composition (curing conditions: curing at 150°C for 60 minutes) was tested after immersion in propylene glycol monomethyl ether acetate (PGMEA), N-methylpyrrolidone (NMP), cyclopentanone, n-hexane, and tetramethylammonium hydroxide aqueous solution (2.38wt%) for 16 hours at 25°C.

[0150] The test results of the above performance are shown in Table 2.

[0151] Table 2

[0152]

[0153] Combining Table 1 and Table 2, we can draw the following conclusions:

[0154] 1) From the comparison of Example 1 and Comparative Example 1, it can be seen that when no nanofiller is added, the composition has no good thixotropic properties, obvious glue overflow occurs in the pit filling experiment, and the weight change rate when immersed in PGMEA, NMP, cyclopentanone, n-hexane, and tetramethylammonium hydroxide aqueous solution is high, indicating that its chemical resistance is poor. However, after adding the nanosilica filler in Example 1, the composition has good thixotropic properties and chemical resistance, no obvious glue overflow, and the addition of the filler can increase the steric hindrance between the epoxy resins, slow down the reaction of the epoxy resin, and make the viscosity increase rate of the composition after 7 days and 14 days lower.

[0155] 2) From the comparison between Comparative Examples 1 and 2, it can be seen that although the viscosity of the cured product can be increased when the oxetane compound is added, the composition does not have good thixotropic properties due to the absence of the nanofiller, and thus the amount of glue overflow is still significant.

[0156] 3) From the comparison between Example 10 and Comparative Example 3, it can be seen that when no cationic stabilizer is added, the adhesive composition solidifies at room temperature and forms a gel state after being placed for 7 days, resulting in a significant decrease in storage stability.

[0157] 4) From the comparison of Examples 1 to 4, it can be seen that adding both silica and pyrolyzed silica as nanofillers is beneficial for obtaining a lower cure shrinkage rate.

[0158] 5) From the comparison of Examples 4 and 5, it can be seen that the addition of an oxetane epoxy monomer to the alicyclic epoxy compound can regulate the curing time, prolong the curing time, significantly increase the viscosity of the adhesive composition, and reduce the amount of glue overflow.

[0159] 6) From the comparison of Examples 5 to 8, it can be seen that the selection of different types of alicyclic epoxy monomers and oxetane epoxy monomers has a certain effect on the viscosity, curing shrinkage, gel formation time, glue overflow and heat resistance of the adhesive composition. Among them, Examples 6 and 7 respectively use CELLOXIDE 2021P and OXIPA, and CELLOXIDE 2021P and OXBP, which can make the adhesive composition exhibit more comprehensive properties suitable for encapsulation.

[0160] 7) Comparison of Examples 5, 9, and 10 shows that CXC-1612, as a cationic initiator, has a faster cure speed and significantly lower shrinkage after curing than SI-110. TPP, as a cationic stabilizer, also has a faster cure speed and lower shrinkage than SI-S, with less overflow.

[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An adhesive composition, characterized in that: The adhesive composition comprises: (A) alicyclic epoxy compound; (B) cationic initiator; (C) cationic stabilizer; (D) nanofiller.

2. The adhesive composition according to claim 1, characterized in that The alicyclic epoxy compound includes one or more of 7-oxabicyclo[4,1,0]heptane-3-carboxylic acid, bis-7-oxabicyclo[4,1,0]heptane, vinylcyclohexene dioxide, dicyclopentadiene dioxide, tetrahydroindene diepoxide, and (3,4,3',4'-diepoxy)bicyclohexane.

3. The adhesive composition according to claim 1 or 2, characterized in that: The (A) component further comprises an oxetane compound, wherein the oxetane compound has a structure shown in Formula 1 or Formula 2: In Formula 1, R1 is a hydrogen atom, a C1-C6 alkyl group, a C1-C6 fluoroalkyl group, an allyl group, a C6-C30 aryl group, a furyl group or a thienyl group; R2 is a C1-C6 alkyl group, a C2-C6 alkenyl group, a C2-C6 alkylcarbonyl group, a C2-C6 alkoxycarbonyl group or a C2-C6 N-alkylcarbamoyl group; In formula 2, R3 and R4 are each independently selected from a hydrogen atom, a C1-C6 alkyl group, a C1-C6 fluoroalkyl group, an allyl group, a C6-C30 aryl group, a furyl group or a thienyl group; L1 is a C1-C6 alkylene group, a poly(alkylene oxide), a C2-C6 alkenylene group, a carbonyl group, a C2-C6 alkylene group containing a carbonyl group, a C2-C6 alkylene group containing a carboxyl group, or a C2-C6 alkylene group containing a carbamoyl group.

4. The adhesive composition according to claim 3, characterized in that: The oxetane compound includes one or more of bis[(3-ethyloxetane-3-yl)methyl]benzene-1,3-dicarboxylate, 4,4-bis[(3-ethyl-3-oxoethyl)methoxymethyl]biphenyl, 3-ethyl-3-oxetanemethanol, 3-ethyl-3-(4-hydroxybutoxymethyl)oxetane, and 3-ethyl-3-[(benzyloxy)methyl]oxetane polymer.

5. The adhesive composition according to claim 3 or 4, characterized in that: The mass ratio of the alicyclic epoxy compound to the oxetane compound is 10:1 to 1:

10.

6. The adhesive composition according to any one of claims 1 to 5, characterized in that: The cationic initiator is selected from sulfonium salt cationic initiators and / or ammonium salt cationic initiators; Preferably, the sulfonium salt cationic initiator has a structure shown in Formula 3: In Formula 3, R5, R6, and R7 are each independently selected from a substituted or unsubstituted C1-C6 alkyl group or a substituted or unsubstituted C6-C20 aryl group, and X1 is selected from Cl - 、BF4 - PF6 - 、N(CF3SO2)2 - 、CH3CO2 - CF3CO2 - CF3SO3 - 、HSO4 - 、SO4 2- 、AsF6 - 、SbF6 - and B(C6F5)4 - One of; The ammonium salt cationic initiator has a structure as described in Formula 4: In formula 4, R8, R9, R 10 , R 11 Each is independently selected from a substituted or unsubstituted C1-C6 alkyl group or a substituted or unsubstituted C6-C20 aryl group, X2 - Selected from Cl - 、BF4 - PF6 - 、N(CF3SO2)2 - 、CH3CO2 - CF3CO2 - CF3SO3 - 、HSO4 - 、SO4 2- 、AsF6 - 、SbF6 - and B(C6F5)4 - One of them.

7. The adhesive composition according to any one of claims 1 to 6, characterized in that: The cationic stabilizer includes one or more of the sulfonium salt compound shown in Formula 5, triphenylphosphine, triethanolamine, and 18-crown ether-6; In formula 5, R 12 to R 16 are each independently a hydrogen atom, a C1-C6 alkyl group, an acetyl group, a C1-C6 alkoxycarbonyl group, a benzoyl group or a benzyloxycarbonyl group, and R 17 and R 18 Each is independently a C1-C6 alkyl, benzyl, o-methylbenzyl, m-methylbenzyl, p-methylbenzyl or naphthylmethyl, and Z is a C1-C6 alkylsulfate.

8. The adhesive composition according to any one of claims 1 to 7, characterized in that: The nanofiller is selected from one or more of silicon dioxide, silicon carbide, boron nitride, diamond, aluminum oxide, aluminum hydroxide, vermiculite, mica, wollastonite, calcium carbonate, titanium dioxide, quartz sand, glass, barium sulfate, zirconium oxide, carbon black and organic fillers; And / or, the particle size of the nanofiller is 10 nm to 100 nm.

9. The adhesive composition according to any one of claims 1 to 8, characterized in that: The adhesive composition comprises, by mass content, 70 wt % to 95 wt % of component (A), 1 wt % to 10 wt % of component (B), 0.1 wt % to 1.0 wt % of component (C), and 0.5 wt % to 30 wt % of component (D).

10. A wafer-level packaging structure, characterized in that: It comprises a silicon substrate and a plurality of grooves on the silicon substrate, wherein the grooves contain chips, and the gaps between the chips and the grooves contain a cured product of the adhesive composition according to any one of claims 1 to 9.

11. The wafer-level packaging structure according to claim 10, characterized in that: The length and width of the groove are 1 to 10 mm respectively, and the depth of the groove is 50 to 300 μm.

12. A method for preparing a wafer-level packaging structure according to claim 10 or 11, characterized in that: The following steps are involved: embedding the chip into the groove of the silicon substrate; injecting the adhesive composition into the gap between the chip and the groove; The adhesive composition is cured to obtain the wafer-level packaging structure.

13. The preparation method according to claim 12, characterized in that: The curing temperature is 100-180° C. and the curing time is 30-180 min.

14. A semiconductor device, comprising the wafer-level packaging structure according to claim 10 or 11 or the wafer-level packaging structure manufactured by the manufacturing method according to claim 12 or 13.